PENGARUH PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DAN KUALITAS BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN DASAR – DASAR PROGRAM KEAHLIAN (DDPK) MANAJEMEN PERKANTORAN KELAS X MP DI SMK SWASTA BUDI AGUNG MEDAN - Naillah Wanza Zein Hasibuan; Nelly Armayanti; Dodi Pramana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of technology has driven the integration of Artificial Intelligence (AI) into the field of education. Based on observations and interviews conducted at SMK Swasta Budi Agung Medan, it was found that most students of Class X MP have utilized AI in the learning process, especially in completing assignments, searching for information, and understanding learning materials. The use of AI has proven to provide ease and effectiveness in learning, although there are still some students who lack confidence in integrating AI in more complex ways due to limited knowledge and concerns about technological errors. The daily test score data shows that students have relatively good learning outcomes, with an average score of 77.39%. The results of this study indicate that, based on the t-test (partial), the use of Artificial Intelligence (X1) has a positive and significant influence on Learning Outcomes (Y), with a calculated t-value greater than the critical t-value (20.545 > 0.0696) and a significance level of 0.001 < 0.05 at a 95% confidence level and 5% alpha. Likewise, Learning Quality (X2) has a positive and significant effect on Learning Outcomes (Y), with a calculated t-value greater than the critical t-value (19.401 > 0.696) and a significance level of 0.001 < 0.05 at a 95% confidence level and 5% alpha. The F-test (simultaneous) results show that the calculated F-value is greater than the F-table value for the influence of X1 on Y (10.093 > 1.66757), with a significance level of 0.001 < 0.05, and for X2 on Y (13.451 > 1.66757) with a significance level of 0.000 < 0.05. The coefficient of determination (R²) obtained is 0.932 or R² = 0.932 x 100% = 93.2%. From the results of this study, it can be concluded that there is a 93.2% influence of the Use of Artificial Intelligence (AI) and Learning Quality on Student Learning Outcomes in the subject of Fundamentals of Vocational Expertise Program (DDPK) in Office Management for Class X MP at SMK Swasta Budi Agung Medan.